DYNAMICS ANALYSIS AND DEVELOPMENT FORECASTING OF THE MAIN SOCIO-ECONOMIC INDICATORS OF THE REPUBLIC OF KAZAKHSTAN - Nurlan Tazhbayev; Zhanna Tutkusheva; Bakhytzhan Blyalov (Izdevnieciba "Baltija Publishing", 2017)
The analysis of the modern condition of economy and bank sector of the Republic of Kazakhstan is carried out in the article. Indicators of gross domestic product (GDP) and investment in the fixed capital in the directions of using are considered, the structure of financial sector is presented.